Pengaruh Brand Image Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Skincare “Skintific” - Atala Cindy Fatya; Destifa Umari Ramadhanti; Rayhan Gunaningrat (Institut Nalanda, 2024)
The purpose of this study is to investigate how consumer decicsion to buy Skintific skincare products are influenced by brand perception and product quality. This study uses quantitative metodhs. Customers of Skintific skincare products made up the full study population. There were 100 responders in the study’s sample. Primary and secondary data are the two types of data that were gathered. Partial Least Square (PLS) using SmartPLS 4.0 software were employed in this investigation. The findings demonstrated that consumers’ decisions to buy Skintific skincare products were not significantly influenced by the brand’s perception. A major factor in customers’ decision to purchase Skintific skincare products is product quality. Thus, in a order to influence more customer purchase decision, Skintific skincare products must maintain their excellent product quality and brand image.